Entrepreneurship, Social Capital, and Institutions: Social and Commercial Entrepreneurship across Nations. (May 2013) - Estrin, Saul; Mickiewicz, Tomasz; Stephan, Ute
We model and test the relationship between social and commercial entrepreneurship drawing on social capital theory. We propose that the country prevalence rate of social entrepreneurship is an indicator of constructible nation–level social capital and enhances the likelihood of individual commercial entry. We further posit that both social and commercial entrepreneurial entry is facilitated by certain formal institutions, namely strong property rights and (low) government activism, albeit the latter impacts each of these types of entrepreneurship differently. We apply bivariate discrete choice multilevel modeling to population–representative samples in 47 countries and find support for these hypotheses.